Establishment of serological neutralizing tests using pseudotyped viruses for comprehensive detection of antibodies against all 18 lyssaviruses - INOUE, Yusuke; KAKU, Yoshihiro; HARADA, Michiko; ISHIJIMA, Keita; KURODA, Yudai; TATEMOTO, Kango; VIRHUEZ-MENDOZA, Milagros; NISHINO, Ayano; YAMAMOTO, Tsukasa; PARK, Eun-sil; INOUE, Satoshi; MATSUU, Aya; et al. (Journal of Veterinary Medical Science, 2024)
Rabies is a fatal zoonotic, neurological disease caused by rabies lyssavirus (RABV) and other lyssaviruses. In this study, we established novel serological neutralizing tests (NT) based on vesicular stomatitis virus pseudotypes possessing all 18 known lyssavirus glycoproteins. Applying this system to comparative NT against rabbit sera immunized with current RABV vaccines, we showed that the current RABV vaccines fail to elicit sufficient neutralizing antibodies against lyssaviruses other than to those in phylogroup I. Furthermore, comparative NT against rabbit antisera for 18 lyssavirus glycoproteins showed glycoproteins of some lyssaviruses elicited neutralizing antibodies against a broad range of lyssaviruses. This novel testing system will be useful to comprehensively detect antibodies against lyssaviruses and evaluate their cross-reactivities for developing a future broad-protective vaccine.